EDUKASI DAN PELATIHAN KADER KESEHATAN UNTUK MENINGKATKAN KEPATUHAN PESERTA PROLANIS - Fadila, Rizki; Retnaningtyas, Ekowati; Dewiyani, AAI Citra; Ningrum, Herlinda Dwi; Purnamasari, Ayu Tyas (Politeknik Kesehatan Kemenkes malang, 2025)
The Chronic Disease Management Program (Prolanis) is an effort to improve the quality of life for chronic disease sufferers through regular health monitoring and proper management. However, the level of adherence of Prolanis participants to follow the program remains a major challenge. One way to improve participant adherence is by involving health cadres who act as a link between participants and healthcare facilities. This Community Service activity aims to implement education and training for health cadres to increase participant adherence in following Prolanis. The results of the Community Service activity show an increase in cadres' knowledge about Prolanis and their skills in communicating with participants. In addition, cadres were educated to carry out measurements of height, weight, Body Mass Index (BMI), as well as blood sugar and blood pressure measurements. It can be concluded that training health cadres plays an important role in improving Prolanis participants' adherence, and this activity is expected to support the success of Prolanis implementation.